War and our world - Keegan, John 1934-2012 (Vintage Books, 1998)
"Is war a natural condition of humankind? What are the origins of war? Is the modern state dependent on warfare? How does war affect the individual, combatant or noncombatant? Can there be an end to war? Keegan addresses these questions with a breathtaking knowledge of history and the many other disciplines that have attempted to explain the phenomenon. The themes Keegan concentrates on in this short volume are essential to our understanding of why war remains the single greatest affliction of humanity in the twenty-first century, surpassing famine and disease, its tractional companions."--Jacket